Thermal Stress Has Minimal Effects on Bacterial Communities of Thermotolerant Symbiodinium Cultures - Díaz-Almeyda, Erika M.; Ryba, Tyrone; Ohdera, Aki H.; Collins, Shannon M.; Shafer, Natali; Link, Caroline; Prado-Zapata, Marcela; Ruhnke, Cara; Moore, Meredith; González Angel, A. M.; Pollock, F. Joseph; Medina, Monica (Frontiers in Ecology and Evolution, 2022)
Algae in the dinoflagellate family Symbiodiniaceae are endocellular photosymbionts of corals and other cnidarians. This close relationship is disrupted when seawater temperature increases, causing coral bleaching eventually affecting entire coral reefs. Although the relationship between animal host and photosymbiont has been well studied, little is known about the bacterial community associated with Symbiodiniaceae in culture. We compared the microbial communities of three isolates from different species of the genus Symbiodinium (formerly known as Symbiodinium clade A) with different ecophysiology, levels of interaction with the animal host, and thermal adaptations. Two species, S. microadriaticum and S. necroappettens, exhibit intermediate thermotolerance, with a decrease of both growth rate and photochemical efficiency with increased temperature. The third species, S. pilosum, has high thermotolerance with no difference in growth rate or photochemical efficiency at 32°C. Microbial communities were characterized after 27 days of growth under control (26°C) and high temperature (32°C). Data shows stronger grouping of bacterial assemblages based on Symbiodinium species than temperature. Microbial communities did not group phylogenetically. We found a shared set of fifteen ASVs belonging to four genera and three families that remained in all three Symbiodiniaceae species. These included Labrenzia, Phycisphaeraceae (SM1A02), Roseovarius, and Muricauda, which are all commonly associated with corals and Symbiodiniaceae cultures. Few ASVs differed significantly by temperature within species. S. pilosum displayed significantly lower levels of microbial diversity and greater individual variability in community composition at 32°C compared to 26°C. These results suggest that bacteria associated or co-cultured with thermotolerant Symbiodinium might play an important role in thermotolerance. Further research on the functional metabolic pathways of these bacteria might hold the key to understanding Symbiodinium’s ability to tolerate thermal stress.